2022
DOI: 10.1177/00220345211062585
|View full text |Cite
|
Sign up to set email alerts
|

Axin2+ PDL Cells Directly Contribute to New Alveolar Bone Formation in Response to Orthodontic Tension Force

Abstract: Wnt–β-catenin signaling plays a key role in orthodontic tooth movement (OTM), a common clinical practice for malocclusion correction. However, its targeted periodontal ligament (PDL) progenitor cells remain largely unclear. In this study, we first showed a synchronized increase in Wnt–β-catenin levels and Axin2+ PDL progenitor cell numbers during OTM using immunostaining of β-catenin in wild-type mice and X-gal staining in the Axin2-LacZ knock-in line. Next, we demonstrated time-dependent increases in Axin2+ P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Axin2 is a direct target of Wnt signaling (Jho et al, 2002;Lustig et al, 2002) and Wnt-responsive cells expressing Axin2 are identified as MSCs in various tissues, including the dental pulp of both mouse incisors and molars in mice (Yuan et al, 2018) and during orthodontic tooth movement (K. Wang et al, 2022). In cementogenesis, Axin2 + cells differentiate into cementoblasts under the regulation of Wnt signaling (Xie et al, 2019), in a similar manner to Gli1 + cells (Xie et al, 2021).…”
Section: The Pdl Contains Diverse Types Of Periodontium Stem/progenit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Axin2 is a direct target of Wnt signaling (Jho et al, 2002;Lustig et al, 2002) and Wnt-responsive cells expressing Axin2 are identified as MSCs in various tissues, including the dental pulp of both mouse incisors and molars in mice (Yuan et al, 2018) and during orthodontic tooth movement (K. Wang et al, 2022). In cementogenesis, Axin2 + cells differentiate into cementoblasts under the regulation of Wnt signaling (Xie et al, 2019), in a similar manner to Gli1 + cells (Xie et al, 2021).…”
Section: The Pdl Contains Diverse Types Of Periodontium Stem/progenit...mentioning
confidence: 99%
“…Axin2 is a direct target of Wnt signaling (Jho et al, 2002; Lustig et al, 2002) and Wnt‐responsive cells expressing Axin2 are identified as MSCs in various tissues, including the dental pulp of both mouse incisors and molars in mice (An et al, 2018; Babb, Chandrasekaran, Carvalho Moreno Neves, & Sharpe, 2017; Bowman, van Amerongen, Palmer, & Nusse, 2013; Lee et al, 2015; van Amerongen, Bowman, & Nusse, 2012). Axin2 + cells in the PDL differentiate into alveolar bone osteoblasts after tooth extraction (Yuan et al, 2018) and during orthodontic tooth movement (K. Wang et al, 2022). In cementogenesis, Axin2 + cells differentiate into cementoblasts under the regulation of Wnt signaling (Xie et al, 2019), in a similar manner to Gli1 + cells (Xie et al, 2021).…”
Section: The Pdl Contains Diverse Types Of Periodontium Stem/progenit...mentioning
confidence: 99%
“…Wnt3A protein applied in the extraction socket increased the number of Wnt‐responsive cells and facilitated bone formation (Yuan et al, 2018). Axin2+ cells in the periodontal tissue were sensitive to orthodontic tension force and were involved with PDL expansion and alveolar bone formation (K. Wang et al, 2022). Furthermore, Axin2+ cells were shown to support postnatal cementogenesis (Xie et al, 2021).…”
Section: In Vivo Identification Of Periodontal Stem Cellsmentioning
confidence: 99%
“…Through this pathway, the increased expression of SIRT1 suppressed Wnt/β-catenin signaling and further inhibited VC ( Chen et al, 2021a ). And Wnt/β-catenin is well verified to play an important role in osteogenesis calcification and alveolar bone remodeling ( Wang et al, 2022 ). Similarly, SIRT1 signaling has been found to be activate during the resveratrol-induced improvement of aortic calcification in ovariectomized rats ( Hammad et al, 2021 ).…”
Section: The Roles Of Sirtuins In Vascular Calcificationmentioning
confidence: 99%